Ocellatin-PT antimicrobial peptides: high-resolution microscopy studies in antileishmania models and interactions with mimetic membrane systems - Oliveira, Mayara (2016)
Although the mechanism of action of antimicrobial peptides (AMPs) is not clear, they can interact electrostatically with the cell membranes of microorganisms. New ocellatin-PT peptides were recently isolated from the skin secretion of Leptodactylus pustulatus. The secondary structure of these AMPs and their effect on Leishmania infantum cells, and on different lipid surface models was characterized in this work. The results showed that all ocellatin-PT peptides have an -helix structure and five of them (PT3, PT4, PT6 to PT8) have leishmanicidal activity; PT1 and PT2 affected the cellular morphology of the parasites and showed greater affinity for leishmania and bacteria-mimicking lipid membranes than for those of mammals. The results show selectivity of ocellatin-PTs to the membranes of microorganisms and the applicability of biophysical methods to clarify the interaction of AMPs with cell membranes.